Risk analysis of ischemic‐type biliary lesions after liver transplant using octogenarian donors. Issue 5 (26th April 2016) - Ghinolfi, Davide; De Simone, Paolo; Lai, Quirino; Pezzati, Daniele; Coletti, Laura; Balzano, Emanuele; Arenga, Giuseppe; Carrai, Paola; Grande, Gennaro; Pollina, Luca; Campani, Daniela; Biancofiore, Gianni; et al.
Abstract : The use of octogenarian donors to increase the donor pool in liver transplantation (LT) is controversial because advanced donor age is associated with a higher risk of ischemic‐type biliary lesions (ITBL). The aim of this study was to investigate retrospectively the role of a number of different pre‐LT risk factors for ITBL in a selected population of recipients of octogenarian donor grafts. Between January 2003 and December 2013, 123 patients underwent transplantation at our institution with deceased donor grafts from donors of age ≥80 years. Patients were divided into 2 groups based on the presence of ITBL in the posttransplant course. Exclusion criteria were retransplantations, presence of vascular complications, and no availability of procurement liver biopsy. A total of 88 primary LTs were included, 73 (83.0%) with no posttransplant ITBLs and 15 (17.0%) with ITBLs. The median follow‐up after LT was 2.1 years (range, 0.7‐5.4 years). At multivariate analysis, donor hemodynamic instability (hazard ratio [HR], 7.6; P  = 0.005), donor diabetes mellitus (HR, 9.5; P  = 0.009), and donor age–Model for End‐Stage Liver Disease (HR, 1.0; P  = 0.04) were risk factors for ITBL. Transplantation of liver grafts from donors of age ≥80 years is associated with a higher risk for ITBL. However, favorable results can be achieved with accurate donor selection. Donor hemodynamic instability, a donor history of diabetes mellitus, and allocation to higher Model for End‐Stage Liver Disease score recipient all increase the risk of ITBL and are associated with worse graft survival when octogenarian donors are used. Liver Transplantation 22 588‐598 2016 AASLD.